PERBAIKAN KAMAR MANDI, PEMASANGAN KERAMIK TERAS DAN PLESTER DINDING PONDOK SANTRI DI PONDOK PESANTREN NURUL HUDA, KP. SOMANG, DS. SOMANG, KEC. PARUNG PANJANG, KAB. BOGOR - JABAR - Taryana Taryana; Yayuk Suprihartini; A Nugroho Budi Rukisman; Pribadi Asih; Hendro Widiarto (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2021)
The purpose of the service at the Nurul Huda Islamic Boarding School located in Somang Village, Parung Panjang District, Bogor Regency, West Java is to empower students together with the community in realizing learning support facilities and infrastructure. This boarding school was chosen as the location of the activity because it was a religious educational institution that has geographical potential and the number of students it has. To support the smooth learning process and the daily life of students in staying in the boarding school environment, the problem was providing a bathroom in which there is a place for bathing, washing and latrines. It was a necessity that should be available in a dormitory and due to limited funds to complete its construction, it cannot be used properly, in order to alleviate and resolve the existing problems that community service activities are carried out in Islamic boarding schools. The method of activity by involving students and the community in improving various learning support facilities. The results of the empowerment carried out have succeeded in building facilities in the form of bathrooms, terrace tiles, and tidying the walls of the Islamic boarding school.